UTILIZATION OF CHARCOAL BRIQUETTE PRINTING MACHINES IN WOOD CHARCOAL CRAFTSMEN AS AN EFFORT TO IMPROVE ECONOMIC EMPOWERMENT - digdo listyadi setyawan; Nasrul - Ilminnafik; Hary - Sutjahjono; intan - hardiatama; mochammad - Asrofi (El-Khidmat, 2024)
In Dawuhan village, Grujugan District, Kab. Bondowoso has a number of wood charcoal Micro, Small and Medium Enterprises (MSMEs), but the production equipment is still simple. The sizes of charcoal produced by MSME partners are usually classified into three A, B and C. Type C wood charcoal is usually thrown away. Currently there are efforts from partners to change the production of class B and C charcoal into charcoal briquettes. However, briquette printing is still done manually, so problems arise due to limited energy and time. The focus of this service is to overcome the limitations of knowledge and technology experienced by a partner named Bpk. Sahawi with methods of providing guidance and counseling as well as providing a charcoal briquette printing machine. There were 20 people involved and evaluations were carried out directly or indirectly. The results of service activities show an increase in human resources for wood charcoal craftsmen through counseling and training by 80%.